On languages generated by spiking neural P systems with weights - Zeng, Xiangxiang; Xu, Lei; Liu, Xiangrong; Pan, Linqiang (Information sciences, 2014)
Spiking neural P systems with weights (WSN P systems, for short) are a class of distributed parallel computing devices inspired from the way neurons communicate by means of spikes. It has been proved that WSN P systems can generate/recognize Turing computable set of numbers (i.e., they are Turing universal as number generators/recognizers). In this work, we investigate the language generation power of WSN P systems, where the set of spike trains of halting computations of a given WSN P system constitutes the language generated by that system. Several relationships of the families of languages generated by WSN P systems with the family of finite languages and the family of regular languages are obtained. The family of recursively enumerable languages is characterized by projections of inverse-morphic images of languages generated by WSN P systems.